DEVELOPMENT OF DIGITAL COMPETENCE OF THE LECTURER IN THE CONTEXT OF PROMOTING ACADEMIC ACTIVITIES - TRACH, Khrystyna; VAKULENKO, Anastasiia (Accents and Paradoxes of Modern Philology, 2026)
The article is focused on analysing the development of digital competences of lecturers in the context of popularising their scientific activities. The contemporary tendencies in the digitalization of education and scientific communications that impact the academic activities of lecturers are analysed. Particular attention is paid to digital platforms and social networks that facilitate the dissemination of scientific research and ensure effective communication with colleagues and students. It is determined that the extensive use of digital resources contributes to increasing the visibility of scientific research and significantly expands opportunities for international cooperation and involvement of new partners in scientific activities. Moreover, the importance of social networks as a tool for enhancing communication between researchers is emphasised, which allows to create new forms of scientific cooperation and popularisation of scientific achievements. Meanwhile, the potential risks associated with the use of digital platforms are analyzed, in particular, high demand for audience attention, potential manipulation of information and data security issues. Developing digital competencies is a prerequisite for ensuring high competitiveness of lecturers in the labour market, as well as for effective research activities in an academic environment where digital technologies are at the forefront. Besides, the study offers an overview of the positive aspects of the active use of digital platforms and social networks to promote and disseminate scientific achievements, including the aforementioned expansion of professional opportunities for lecturers, establishment and improvement of communication with students and colleagues, and general increase of scientific work visibility. The results of the research among lecturers prove a high level of awareness of the importance of digital tools in research and their intensive use in practice. The main tools actively used are publication platforms and social networks, although some difficulties related to lack of time, data security issues, and the necessity for additional training were also revealed. The effective usage of digital technologies requires supporting lecturers by providing them with supplementary digital literacy courses and access to innovative digital tools to facilitate the integration of digital competencies into their professional activities.